Functional brain responses to emotional faces after three to five weeks of intake of escitalopram in healthy individuals: a double-blind, placebo-controlled randomised study - Armand, Sophia; Langley, Christelle; Johansen, Annette; Ozenne, Brice; Overgaard-Hansen, Oliver; Larsen, Kristian; Jensen, Peter Steen; Knudsen, Gitte Moos; Sahakian, Barbara Jacquelyn; Stenbæk, Dea Siggard; Fisher, Patrick MacDonald (Scientific reports, 2024)
Short-term intake of selective serotonin reuptake inhibitors (SSRIs) modulates threat-related amygdala responses in healthy individuals. However, how SSRI intake over a clinically relevant time period modulates threat-related amygdala responses is less clear. In a semi-randomised, double-blind, placebo-controlled study of 64 healthy individuals (SSRI n = 32, placebo n = 32), we examined the effect of 3–5 weeks of SSRI escitalopram (20 mg daily) on brain response to angry, fearful and neutral faces using BOLD fMRI. Data was analysed using a whole-brain region-wise approach extracting standardised effects (i.e., Cohen’s D). The study was conducted at the Copenhagen University Hospital. A priori, we hypothesised that SSRI would attenuate amygdala responses to angry and fearful faces but not to neutral ones. Whether SSRI modulates correlations between amygdala responses to emotional faces and negative mood states was also explored. Compared to placebo, 3–5 weeks of SSRI intake did not significantly affect the amygdala response to angry, fearful, or neutral faces (|Cohen’s D|< 0.2, P FWER = 1). Whole-brain, region-wise analyses revealed significant differences in frontal (|Cohen’s D|< 0.6, P FWER < .01) and occipital regions (|Cohen’s D|< 0.5, P FWER < .01). SSRI did not modulate correlations between amygdala responses to emotional faces and negative mood states. Our findings indicate that a 3–5 week SSRI intake impacts cortical responses to emotional stimuli, an effect possibly involved in SSRI’s therapeutic efficacy. Trial registration Clinical Trials NCT04239339.